2012
DOI: 10.1016/j.bpj.2011.10.048
|View full text |Cite
|
Sign up to set email alerts
|

Blood Clot Formation under Flow: The Importance of Factor XI Depends Strongly on Platelet Count

Abstract: A previously validated mathematical model of intravascular platelet deposition and tissue factor (TF)-initiated coagulation under flow is extended and used to assess the influence on thrombin production of the activation of factor XI (fXI) by thrombin and of the activation of factor IX (fIX) by fXIa. It is found that the importance of the thrombin-fXIa-fIXa feedback loop to robust thrombin production depends on the concentration of platelets in the blood near the injury. At a near-wall platelet concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
74
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 47 publications
5
74
0
1
Order By: Relevance
“…Importantly, platelet concentrations in wallattached thrombi that form under flow are 50-to 200-fold greater than those found in whole blood, a complexity that distinguishes microfluidic flow studies from test tube studies. [24][25][26] Recently, a phase 2 trial demonstrated that FXI-antisense oligonucleotide (FXI-ASO) reduced FXI levels and decreased the incidence of deep vein thrombosis (DVT) after knee arthroplasty without increasing bleeding, thus providing evidence that FXIa can contribute to thrombosis in humans. 27 However, postoperative bleeding in knee arthroplasty is relatively uncommon, and the rate of bleeding with FXI-ASO was not significantly lower than that seen with enoxaparin.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, platelet concentrations in wallattached thrombi that form under flow are 50-to 200-fold greater than those found in whole blood, a complexity that distinguishes microfluidic flow studies from test tube studies. [24][25][26] Recently, a phase 2 trial demonstrated that FXI-antisense oligonucleotide (FXI-ASO) reduced FXI levels and decreased the incidence of deep vein thrombosis (DVT) after knee arthroplasty without increasing bleeding, thus providing evidence that FXIa can contribute to thrombosis in humans. 27 However, postoperative bleeding in knee arthroplasty is relatively uncommon, and the rate of bleeding with FXI-ASO was not significantly lower than that seen with enoxaparin.…”
Section: Introductionmentioning
confidence: 99%
“…This model is adapted from our earlier models of arterial thrombosis (39)(40)(41) and shares numerous features of those models. The models involve the same set of coagulation enzyme reactions and the same reaction rate constants.…”
Section: Introductionmentioning
confidence: 99%
“…Assumptions 1 to 6 are essentially unchanged from assumptions in our arterial thrombosis models; see (39,41) for further discussion of them. Assumptions 7 to 10 are either completely new to the venous thrombosis situation or are substantial modifications to those in (39,41).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This late stage participation of thrombin-mediated activation of FXI has also been theoretically predicted (54). The FXI antibody O1A6 inhibits FXIIa activation of FXI and disrupts the FXI-dependent thrombin amplification loop by inhibiting FXIa generation of FIXa and subsequent FXa activation (Fig.…”
mentioning
confidence: 99%